The Development of Physics Teaching Materials Based on Local Wisdom to Train Saraba Kawa Character (Jurnal Pendidikan IPA Indonesia, 2018)
This research came up from the unavailability of the physics teaching materials containing the local wisdom of Tabalong Regency society, South Kalimantan, and the less optimal character education in the learning process. Therefore, the research and development on the physics teaching materials based on the local wisdom of Tabalong regency, South Kalimantan to train saraba kawa character were conducted. The objective of this study was to produce feasible physics teaching materials integrated with the local wisdom based on the aspects of validity, practicality, effectivity, and character achievement. This research type is a research and development using ADDIE model. The subjects of the try out were 36 grade X students of MIPA in 4 SMA Negeri 2 Tanjung Tabalong Regency. The instruments used in this study were validation sheet, response questionnaire, student achievement results, and character observation sheet. The results showed that: (1) the validity of the teaching materials based on its content and appearance was in a good category, (2) the practicality of the teaching material categorized as very practical, (3) the effectiveness of the medium categorized as very practical, (4) and the achievement of saraba kawa character categorized as very good. It concluded that the physics teaching materials based on the local wisdom to train saraba kawa character is feasible for physics learning.